RANCANG BANGUN PANEL SURYA BERBASIS LIMBAH RUMAH TANGGA UNTUK KEBUTUHAN PENERANGAN JALAN RW 3 KELURAHAN BERGASLOR, SEMARANG - Muhamad Juli Saputra; Muhamad Idrokul Fahmi; Ahmad Ramdhani; Sahrul Maulana Rozaki; Hamdan Ramadan; Muhamad Safi’i (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
Abstract Electricity is a source of energy necessary to support various kinds of human activities, one of which is solar power plants. Solar power plants are power plants that convert solar energy into electrical energy. Solar power plants are classified as renewable energy. Solar power plants using household waste are a special attraction, but many people still cannot make maximum use of them due to limited knowledge and knowledge. So there is a need for education on using and empowering household waste to create designs for solar energy for street lighting applications. Through the Community Service program, activities are carried out in the Krajan RT 06, RW 03, Bergaslor Village, Bergas District, Semarang Regency. Community Service activities are carried out through stages of education, training, and direct design practice to resolve problems complained by partners. The household waste-based solar panel prototype consists of a 5 mm thick iron plate as a solar panel holder, a 5 x 5 cm hollow piece as a pole, and acrylic. Solar panel 1.2 x 1 m. Used VCD cassettes are used to wind up copper wire with a diameter of 1.5 mm, and acrylic waste for solar panel modules. The result of this activity is a solar panel prototype made by utilizing household waste with a solar panel capacity of 120 Watts. These results confirm that solar panels made from waste materials can support street lighting in the Krajan RT 06, RW 03, Bergaslor Village, Bergas District, Semarang Regency.